Implementasi Webqual dan End-User Computing Satisfaction untuk Menganalisis Kualitas dan Kepuasan Pengguna Website - Ibnur Rusi (ISB Atma Luhur, 2022)
A website is one of the choices of means used to facilitate an agency in providing information. A quality website is a website that can give satisfaction to users. The availability of features on the website that suit user needs, attractive website appearance, easy-to-remember steps, and feedback are some of the essential points that can satisfy users. Madrasah Aliyah Negeri (MAN) Singkawang is a school that uses a website to provide information; until now, the MAN Singkawang website has never measured the quality of the website, so schools do not know the user satisfaction. This study aims to implement the Webqual and EUCS methods to determine the effect of website quality on end-user satisfaction. The test is carried out through several levels, namely, validity test, reliability test, t-test, F test, and coefficient of determination test. The results of the statement test stated that all questions were valid and reliable; there was a positive and significant influence of website quality through the independent variables Webqual and EUCS on the dependent variable user satisfaction (satisfaction), either partially or simultaneously. The coefficient of determination test results obtained a value of 58.8%, meaning that the ability of the independent variable to provide an explanation related to the dependent variable is relatively high. In other words, the independent variable offers a lot of information needed to predict the dependent variable. As for the calculation of user satisfaction on the MAN Singkawang website, a user satisfaction value of 83% is obtained. This value indicates that the students of MAN Singkawang are very satisfied through the quality provided on the MAN Singkawang website.